Parasite communities and infection levels of the invasive Chinese sleeper Perccottus glenii (Actinopterygii: Odontobutidae) from the Naab river basin, Germany. Issue 6 (4th November 2016) - Kvach, Y.; Janáč, M.; Nehring, S.; Ondračková, M.; Jurajda, P.
Abstract: The Chinese sleeper ( Perccottus glenii ), an invasive Asian fish, was first registered in Germany in 2009 (westernmost extent of its invasive range). We sampled Chinese sleepers from two localities on the Bücherlgraben creek (a tributary of the River Naab) in south-eastern Germany in November 2015 and examined them for parasite infection. Twelve taxa were registered, including ciliates (unidentified Trichodina ), a monogenean, three cestode species, two digenean taxa, two acanthocephalan species, two nematode species and one mollusc glochidia. Infracommunities consisted of 1–5 species, with 10% of fish uninfected. Three parasite species ( Acanthocephalus anguillae, Gyrodactylus luciopercae and Pseudocapillaria tomentosa ) were recorded on Chinese sleepers for the first time. The results highlight the important role of the Chinese sleeper as a second intermediate host in the life cycle of heron and grebe parasites. The Chinese sleeper parasite community displayed low homogeneity at both localities sampled, with allogenic parasites (metacercariae and mesocercoids) mostly shared. Differences between localities were mainly caused by autogenic parasites. No invasive parasites associated with the Chinese sleeper were observed in the study area, all parasites being representatives of European fauna. This supports the hypothesis of introduction via the aquarium trade or through transport with commercial fish.